Cosmetic and medical tattoos : technique and application - Serup, Jørgen; Ercegovac, Maja; Bennoun, Ina; Hvas, Diana (Current problems in dermatology / series editors Peter Itin, Gregor B.E. Jemec, 2023)
Discover more about permanent make-up and medical tattooing in the new book 'Cosmetic and Medical Tattoos', part the book series 'Current Problems in Dermatology'. This comprehensive book covers a broad range of techniques and applications; brows, eyeliners, lips; areola and nipple after breast surgery, scar camouflage and 3D reconstruction. Contributions are made by internationally esteemed permanent make-up masters and medical experts. This collection is a milestone and unique source of information to cosmetic tattoo practitioners as well as medical specialists, who recognise the importance of aesthetic intervention to complement otherwise successful treatment.